2012
DOI: 10.1371/journal.pone.0035642
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine D2 Receptor Gene in Lamprey, Its Expression in the Striatum and Cellular Effects of D2 Receptor Activation

Abstract: All basal ganglia subnuclei have recently been identified in lampreys, the phylogenetically oldest group of vertebrates. Furthermore, the interconnectivity of these nuclei is similar to mammals and tyrosine hydroxylase-positive (dopaminergic) fibers have been detected within the input layer, the striatum. Striatal processing is critically dependent on the interplay with the dopamine system, and we explore here whether D2 receptors are expressed in the lamprey striatum and their potential role. We have identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 55 publications
3
48
0
Order By: Relevance
“…To determine how the dopaminergic innervation of the GPh affects neuronal firing, we first examined the dopamine receptor expression. In lamprey, dopamine D2 receptors are highly expressed in the striatum as well as in the GPh (25). In situ hybridization confirmed that neurons in the GPh express D2 receptor mRNA ( Fig.…”
Section: Direct Glutamatergic Projections From the Pallium (Cortex) Ementioning
confidence: 61%
See 2 more Smart Citations
“…To determine how the dopaminergic innervation of the GPh affects neuronal firing, we first examined the dopamine receptor expression. In lamprey, dopamine D2 receptors are highly expressed in the striatum as well as in the GPh (25). In situ hybridization confirmed that neurons in the GPh express D2 receptor mRNA ( Fig.…”
Section: Direct Glutamatergic Projections From the Pallium (Cortex) Ementioning
confidence: 61%
“…Templates for in vitro transcription were prepared by PCR amplification. For the dopamine D2 receptor probe, a 660-bp fragment was obtained using 5′-TGCTCATATGCCTCATCGTC-3′ forward and 5′-TCAAGCTTTGCACAATCGTC-3′ reverse primers (25). The amplified cDNA fragments were cloned into a pCRII-TOPO vector (Invitrogen), cleaned, and confirmed by nucleotide sequencing (KIGene core facility at Karolinska Institutet).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used in lampreys, salamanders, rats, and human to label DA neurons (manufacturer's information) (22,28,(69)(70)(71)(72)(73). The 22941 TH antibody was used here on human tissue based on its successful use by Parent et al (74).…”
Section: Methodsmentioning
confidence: 99%
“…Elements of this neuromodulatory organization may be conserved, because the striatum of non-mammalian vertebrates (lamprey, amphibians, reptiles, and birds) also receives a large dopaminergic projection from the homolog of the SNc/VTA and express D 1 and D 2 receptors (Reiner et al, 1998;Chu et al, 2001;Pombal et al, 2007;Robertson et al, 2012). Furthermore, in turtles and birds, dopamine excites striatal neurons that express D 1 receptors and inhibits neurons that express D 2 receptors (Ding and Perkel, 2002;Barral et al, 2010).…”
Section: Introductionmentioning
confidence: 99%